2022
DOI: 10.1002/smll.202201205
|View full text |Cite
|
Sign up to set email alerts
|

Using Wool Keratin Derived Metallo‐Nanozymes as a Robust Antioxidant Catalyst to Scavenge Reactive Oxygen Species Generated by Smoking

Abstract: Self‐assembled nanostructures based on biomolecules (e.g., proteins and amino acids) and metal ions have promising applications in mimicking the nanostructure, properties, and functions of natural enzymes. Herein, a metal ion‐mediated self‐assembly method for constructing catalytically active Cu‐wool‐keratin (CuWK) two‐dimensional nanozymes is presented. Specifically, by introducing copper ions as abiological cofactors, WK can serve as a protein scaffold to design and create Cu catalytic sites. The optimized h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 43 publications
0
9
0
Order By: Relevance
“…Wool powder, cotton fabric, and polyester fabric showed typical characteristic absorption bands of protein, cellulose, and polyethylene terephthalate, respectively. Wool powder showed its characteristic peaks at 3284 cm –1 (stretching vibration of N–H or O–H), 1648 cm –1 (stretching vibration of CO) and 1526 cm –1 (the stretching vibration of C–N, the in–plane bending vibration of N–H) . These three peaks are attributed to the characteristic functional groups of protein, which correspond to Amide A, Amide I, and Amide II, respectively .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Wool powder, cotton fabric, and polyester fabric showed typical characteristic absorption bands of protein, cellulose, and polyethylene terephthalate, respectively. Wool powder showed its characteristic peaks at 3284 cm –1 (stretching vibration of N–H or O–H), 1648 cm –1 (stretching vibration of CO) and 1526 cm –1 (the stretching vibration of C–N, the in–plane bending vibration of N–H) . These three peaks are attributed to the characteristic functional groups of protein, which correspond to Amide A, Amide I, and Amide II, respectively .…”
Section: Resultsmentioning
confidence: 99%
“…Wool powder showed its characteristic peaks at 3284 cm −1 (stretching vibration of N−H or O−H), 1648 cm −1 (stretching vibration of C�O) and 1526 cm −1 (the stretching vibration of C−N, the in−plane bending vibration of N−H). 21 These three peaks are attributed to the characteristic functional groups of protein, which correspond to Amide A, Amide I, and Amide II, respectively. 22 For pristine cotton fabric, absorption bands centered at 3335 and 3291 cm 26 Both the coated cotton fabrics and polyester fabrics displayed characteristic peaks of wool powder (Figure 2c), including Amide I and Amide II, manifesting that the wool powder was successfully coated on fabrics.…”
Section: Characterization Of Wool Powder Treated Fabricsmentioning
confidence: 99%
“…Simultaneously, Xu et al presented CuWK nanozymes constructed by the self-assembly of wool keratin, and metal ions with excellent antioxidant capacities were further used as a new additive into a cigarette filter to remove the produced ROS from the burning of tobacco. 153 Liu et al demonstrated a biochar nanozyme derived from silkworm excrement, which possessed antioxidant abilities to scavenge excess free radicals, including ROS and RNS (Fig. 6A).…”
Section: Nanozymes For the Prevention Of Respiratory Diseasesmentioning
confidence: 99%
“…The center consists of four histidine (His) and one arginine (Arg) residues involved in the coordination of Cu . Drawing inspiration from its structural attributes, researchers have devised various Cu-containing nanomaterials that exhibit exceptional SOD-like enzyme activity. However, the potential long-term toxicity associated with copper retention in the body has limited the use of Cu-containing nanomaterials for disease treatment. To mitigate the potential adverse effects of this heavy metal on organisms, one feasible strategy involves reducing the size of nanomaterials .…”
Section: Introductionmentioning
confidence: 99%